Discrimination of heating and frying vegetable oils based on UPLC/Q-TOF MSMS and chemometrics. (February 2021) - Li, Zixiang; Sun, Yongzhi; Dong, Feng; Yu, Qingli; Fan, Lina; Zhao, Jiali; Wang, Maoqing
Graphical abstract: Highlights: Frying and heating changed numerous compounds of vegetable oils. Different vegetable oils have common markers during heating and frying. Each type of vegetable oil has its own unique markers. The panel of common and unique markers can distinguish used frying oil. Abstract: Fried foods have potential adverse effects on health. However, the compounds produced during the process of frying in different vegetable oils are unknown. In this work, ultra performance liquid chromatography (UPLC), quadrupole time-of-flight mass spectrometry (Q-TOF MSMS) and chemical pattern recognition analysis was first conducted to analyze the changes in compounds in 8 different vegetable oils before and after thin-layer heating (without food) and to reveal the potential markers of oil used for deep-frying food. Then, these markers were validated in used frying oil. Our results of principal component analysis (PCA), partial least-squares discriminant analysis (PLS-DA) indicated that both thin-layer heating and deep-frying significantly change the compounds of vegetable oils. Thirty-six of the markers associated with thin-layer heating from the 8 different oils were identified in used frying oils and can be used as common markers of oil used for deep-frying. Additionally, 22 markers detected in individual vegetable oils provided unique markers of used frying oils. These markers can be used to distinguish used frying oil and have the potential to reveal the associated physiological harm.